TANGGUNG JAWAB ORANG TUA DALAM MENGATASI KESULITAN BELAJAR ANAK SEBAGAIMANA YANG TERSIRAT DALAM LIMA NIKĀYA - Nurhayanti, Slamet; Widiyono; Dewi, Sukhitta (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2024)
The purpose of this research is to find out the responsibility of parents in overcoming children's learning difficulties according to the general view and implied in the five Nikāyas. The research method used is the method of a literature study. The data collection is done by looking for data from various sources such as magazines, books, articles, and journals. After the data collection, next is the data processing. The data collected in this study were analyzed using a synthesize checklist analysis consisting of preliminary, follow-up and final syntheses, taking into account the elements of text, context and discourse. The results of this study are that the responsibility of parents in overcoming children's learning difficulties is not only by providing education. Parents are responsible as motivators, mentors, and facilitators. The active role of parents in overcoming children's learning difficulties will have an influence on children's learning outcomes. The form of parental responsibility in overcoming children's learning difficulties as implied in the Five Nikāyas is not only to support children with good facilities, but to overcome children's learning difficulties by educating, as an encouragement, support, and guide.